Food Security in the Wake of Perennial Crop Farming. Paradoxes Underlying Commercial Agriculture in Kigezi. - Chama, Julius (Kabale University, 2023)
This study critically examines the contribution of tea growing in Kigezi region and how it affects the growth of other crops that are meant for food consumption. It underscores the performance of tea as a cash crop and also as a means of foreign exchange for the country as well as a source of employment. This study establishes that the tea sector has not in any way affected food security in the region of Kigezi and has instead improved house hold incomes, been a source of employment and boosted revenue for households. The sector has however registered some challenges like limited faith among the out growers who prefer their own traditional crops. There have also been challenges of lack of c ordination from stake holders like NEMA, the district local governments and government ministries, departments and agencies. The study recommends to government that policy makers make a comprehensive tea policy that stream lines conflicting agencies and also learn best practices from neighbouring countries like Kenya where the sector has performed immensely well. Farmers also need constant sencitizatin on the benefits of the cash crop.